Differential response to targeted acupuncture by gender in patients with gastrointestinal cancer cachexia: secondary analysis of a randomized controlled trial. Issue 1 (February 2020) - Yoon, Saunjoo L; Grundmann, Oliver; Williams, Joseph J; Wu, Samuel S; Leeuwenburgh, Christiaan; Huo, Zhiguang; George, Thomas J
Background: Cancer cachexia (CC) is a significant contributor to mortality and morbidity in patients with gastrointestinal (GI) cancer. Treatment options to prevent or halt the progression of CC are limited. Targeted acupuncture (TA) was used in GI patients with CC to evaluate for a potential gender effect. Patients and methods: Participants ( n  = 30) were recruited from two outpatient clinics in the northern central part of Florida. All participants were diagnosed with CC and GI cancers. A randomized, single-blind, placebo-controlled clinical trial was used to compare TA to non-targeted acupuncture (NTA) over the course of 8 weeks. Primary endpoints were weight and body composition changes measured by bioelectrical impedance analysis (BIA) and biomarker analysis (tumor necrosis factor (TNF)-α and leptin). Herein, gender differences across and within TA and NTA groups were examined as a secondary analysis. Results: A significant ( p  = 0.026) interaction between weight and gender was noted, which manifested in a non-significant increase in the male intervention (MI) group, while TNF-α levels significantly increased by gender ( p  = 0.028) and group ( p  = 0.006) over the course of the study. All other groups either lost or did not change weight. The extracellular-to-intracellular water (ECW/ICW) ratio was significantly elevated for the TA group ( p  = 0.02) and for males ( p  = 0.009) at completion of the study. TNF-α and leptin levels were positively correlated within the MI group at the end of the study. Conclusion: A decrease in leptin in the MI group corresponded to higher appetite and weight gain. The elevated ECW/ICW ratio indicates an inflammatory response in the MI group. This gender-specific response may be based on hormone-specific regulation of food intake. Further studies with larger sample sizes are required to support the results.